(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article explores the cognitive mechanisms behind how we understand the meaning of words. It argues that conceptual derivation operations play a crucial role in interpreting the meaning of lexical units (words). These operations involve two main directions:This refers to assigning a category to an object or concept. This process creates new knowledge by extending the existing meaning of a word.This involves expressing an opinion or evaluation alongside the core meaning of a word. It goes beyond simply identifying something and conveys the speaker’s attitude or judgment.The article highlights the concept of "conceptual alignment" as essential for establishing connections between different concepts during interpretation. This alignment can be achieved through:Associative agreement: This relies on similarities or connections based on proximity in time or space.Logical agreement: This is based on logical reasoning and connections between concepts.The interpretation process is further influenced by the specific category a word belongs to (e.g., natural objects, artifacts). The characteristics of these categories determine how words within them combine and how their meanings differentiate.The article concludes by discussing how word meanings change and develop over time. It emphasizes the concept of polysemy (multiple meanings) and how new meanings arise through processes like extension, where a word’s meaning broadens from concrete to abstract or specific to general.